Lipid-Coated Polymeric Nanoparticles for the Photodynamic Therapy of Head and Neck Squamous Cell Carcinomas - Valeri Roschenko; Abdallah M. Ayoub; Konrad Engelhardt; Jens Schäfer; Muhammad Umair Amin; Eduard Preis; Robert Mandic; Udo Bakowsky (MDPI AG, 2023)
Next to alcohol and tobacco abuse, infection with human papillomaviruses (HPVs) is a major risk factor for developing head and neck squamous cell carcinomas (HNSCCs), leading to 350,000 casualties worldwide each year. Limited therapy options and drug resistance raise the urge for alternative methods such as photodynamic therapy (PDT), a minimally invasive procedure used to treat HNSCC and other cancers. We prepared lipid-coated polymeric nanoparticles encapsulating curcumin as the photosensitizer (CUR-LCNPs). The prepared CUR-LCNPs were in the nanometer range (153.37 ± 1.58 nm) and showed an encapsulation efficiency of 92.69 ± 0.03%. Proper lipid coating was visualized using atomic force microscopy (AFM). The CUR-LCNPs were tested in three HPVpos and three HPVneg HNSCC lines regarding their uptake capabilities and in vitro cell killing capacity, revealing a variable but highly significant tumor cell inhibiting effect in all tested HNSCC cell lines. No significant differences were detected between the HPVpos and HPVneg HNSCC groups (mean IC50: (9.34 ± 4.73 µmol/L vs. 6.88 ± 1.03 µmol/L), suggesting CUR-LCNPs/PDT to be a promising therapeutic option for HNSCC patients independent of their HPV status.